Are SWFs welcome now? - Veljko Fotak; William Megginson (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
This Perspective documents the change in attitudes of Western governments to foreign direct investment from sovereign wealth funds. The authors propose an analysis of sovereign wealth fund investments and their impact on target firms in order for recipient governments to formulate the proper regulatory response to sovereign direct investment.
Keywords: 330